Do sustainable food system innovations foster inclusiveness and social cohesion? A comparative study - Hennchen, Benjamin; Schäfer, Martina (Frontiers in Sustainability, 2022)
Existing food systems are not only responsible for severe environmental damage, but also face press-ing social challenges, with people having uneven access to safe and healthy food, good working con-ditions, and political participation. These socio-ethical aspects play a key role in successful food tran-sitions. So far, aspects of social cohesion and inclusiveness within social food innovations have rarely been analyzed in more depth. Many social innovations have emerged over the last few decades, such as land cooperatives, farm leasing models, community-supported agriculture, or citizen shareholder companies. Expectations towards these financing models vary from facilitating more investment in a sustainable and socially responsible agri-food sector and a shift towards more local food to the crea-tion of transparent relationships between food producers and consumers. It is against this backdrop that this paper compares three different food innovations—citizen shareholder companies, communi-ty-supported agriculture, and food co-ops—regarding their inclusiveness, the degree of member in-volvement, and the quality of experienced connectedness. Empirically, this paper draws on quantita-tive and qualitative data, including an online survey, two focus group discussions, and a broad litera-ture search. Findings reveal that all food innovations show a rather low level of inclusiveness, alt-hough efforts are being made to overcome barriers to access. Food innovations generate social cohe-sion between different actors along the value-added chain, which is constituted differently in a more service-oriented versus a community-oriented model. Overall, these innovations provide key momen-tum towards the dominant food regime by rewarding producers for sustainable practices, establishing stronger producer–consumer relationships, and motivating consumers to assume shared responsibility. Based on the different approaches adopted, we consider the food innovations as complementary for food system transitions.